2016
DOI: 10.1080/02770903.2016.1242138
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the sensation of activity limitation and the results of functional assessment in asthma patients

Abstract: In response to questions about limitation of activity, patients do not specifically answer mentioning physical limitation but rather the psychological burden associated with this constraint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…We found a significant correlation between SPD and depression and anxiety scores in our asthma patients, although, interestingly, only age, anxiety, and FEV 1 showed significant associations with the number of SPD. Similarly, Vermeulen et al recently reported that psychological burden was the major activity‐limiting factor for asthma patients . According to Herrmann, it is unlikely that age affects HADS scores.…”
Section: Discussionmentioning
confidence: 97%
“…We found a significant correlation between SPD and depression and anxiety scores in our asthma patients, although, interestingly, only age, anxiety, and FEV 1 showed significant associations with the number of SPD. Similarly, Vermeulen et al recently reported that psychological burden was the major activity‐limiting factor for asthma patients . According to Herrmann, it is unlikely that age affects HADS scores.…”
Section: Discussionmentioning
confidence: 97%
“…1 CRS is a clinically challenging disease; as in asthmatic patients, symptoms lack good correlation with objective measurements because of the lack of a gold standard. 2,3 This might be caused by an underlying variation of endotypes leading to a common phenotype 4 and results in a discrepancy of estimates of prevalence based on either symptoms or objective measures. 5 Current data on the prevalence of CRS based on the EPOS symptombased definition show a prevalence of 5.5% in Brazil, 6 8% in China, 7 11% in Europe 8 and Korea, 9 and 12% in the United States.…”
mentioning
confidence: 99%
“…Activity limitation is more common in FE (OR 3.2) than nFE patients, where patients classified as hFE had the highest probability (OR 3.8). In this context, it should be taken into consideration that there is a psychological component that can increase the intensity of the perceived limitation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%